Trophic consistency of supraspecific taxa in below‐ground invertebrate communities: Comparison across lineages and taxonomic ranks. (8th March 2019) - Potapov, Anton M.; Scheu, Stefan; Tiunov, Alexei V.
Abstract: Animals that have similar morphological traits are expected to share similar ecological niches. This statement applies to individual animals within a species and thus species often serve as the functional units in ecological studies. Species are further grouped into higher‐ranked taxonomic units based on their morphological similarity and thus are also expected to be ecologically similar. On the other hand, theory predicts that strong competition between closely related species may result in differentiation of ecological niches. Due to high diversity and limited taxonomic expertise, soil food webs are often resolved using supraspecific taxa such as families, orders or even classes as functional units. Here, we tested the trophic differentiation and consistency of supraspecific taxa across major lineages of temperate forest soil invertebrates: Annelida, Chelicerata, Myriapoda, Crustacea and Hexapoda. Published data on stable isotope compositions of carbon and nitrogen were used to infer basal resources and trophic level, and explore the relationship between taxonomic and trophic dissimilarity of local populations. Genera and families had normal and unimodal distributions of isotopic niches, suggesting that supraspecific taxa are trophically consistent. The isotopic niche of local populations varied considerably resulting in large overlap of niches among species. Within the same genus, the effect of species identity on stable isotope composition of populations was not significant in 92% of cases. More than 50% of the variability in Δ 15 N values (trophic level) across lineages was explained by classes and orders, while the variability in Δ 13 C values (basal resources) was explained mostly by families and genera. The variability in stable isotope composition in Chelicerata and Hexapoda was explained by lower taxonomic ranks than in Myriapoda. We compiled a comprehensive list of mean Δ 13 C and Δ 15 N values of invertebrate taxa from temperate forest soils allowing to refine soil food web models when measurements of trophic niches of local populations are not feasible. Supraspecific taxa are meaningful as trophic nodes in food web studies, but the consistency varies among taxa and the choice of taxonomic resolution depends on the research question; generally, identification of taxa should be more detailed in more diverse taxonomic groups. A plain language summary is available for this article. Abstract : Plain Language Summary